La sinonimia, la polisemia y la hiperonimia en el lenguaje jurídico de la Unión Europea: el caso de las citaciones judiciales - Acuyo Verdejo, María Carmen (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper aims at identifying and describing the main terminological problems arising from the continuing harmonisation of the different national legislations within the European Union. This has resulted in the creation of a new specialised language, that of European Law, which can cause synonymy, polysemy and hyperonymy to emerge when contacting with national legal languages. Both the comprehension and the quality of the translated text can be drastically affected by these phenomena. We illustrate this problem taking, as a point of reference, summons from two different legal systems: the Spanish and the Italian one. Within these texts special attention has been paid to those terms related to the text type used for the summons, the person summoned, and the type of text with which the person in question is summoned. Finally, some strategies are outlined to help the translator to solve these terminological pro blems.